Postoperative vault hematoma following vaginal hysterectomy: case reports - Gupta, Amit; Verma, Tanu; Gupta, Bharti; Vij, Anju; Kumar, Rajinder (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Postoperative vault hematoma is almost a universal consequence of gynaecologic surgery. It usually occurs after vaginal or abdominal hysterectomy. At one end there can be are minimal collection of peritoneal fluid or blood which is clinically insignificant whereas at the other end is the hematoma and abscess requiring active intervention for the patient to recover. We here present two cases of vault hematoma following vaginal hysterectomy which were reported to our institution in recent times. In both cases hematomas were infected. Ultrasonography was used to accurately identify and define the extent of hematomas. The patients underwent vault exploration and drainage. Post-operative period remained uneventful. Postoperative vault hematoma can be diagnosed in the early postoperative period of gynaecologic surgery. It is important to consider the possibility of vault haematoma in patients with persistent fever and vaginal bleeding after hysterectomy. The hematoma cavity can be easily entered to drain hematoma or abscess completely, expediting the recovery of the patient. Refining surgical techniques will significantly reduce the risk of vault hematoma.